Survei Tingkat Kesegaran Jasmani Siswa SMK Negeri 1 Kabupaten Sinjai: Survei Tingkat Kesegaran Jasmani Siswa SMK Negeri 1 Kabupaten Sinjai - Wahyudin, Wahyudin; Hasanuddin, Hasanuddin; Syahruddin, Syahruddin (Indonesia, 2023)
This descriptive research aims to determine students' physical fitness when participating in extracurricular activities at SMK Negeri 1 Sinjai. The population of this study were all extracurricular students in class XI Boys at SMK Negeri 1 Sinjai, with a sample size of 20 male students selected using cluster sampling. Student data was collected using the Indonesian Physical Fitness Test (TKJI) method. The research results showed that the physical fitness level of extracurricular students at SMK 1 Sinjai was in the good category, the results obtained were 45.0%, moderate 50.0%, and poor 5.0%. In accordance with the results of this research, it is recommended to all parties involved in this matter to maintain and further improve it, in this case the principal pays more attention to the existing facilities and infrastructure at SMK Negeri 1 Sinjai, as well as to supervisors and teachers. coaches to expand their knowledge to be more innovative and creative, as well as parents and families to always support their children in sports activities